2000
DOI: 10.1352/0895-8017(2000)105<0118:aitfcw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Integration Training for Children With Autism: No Behavioral Benefits Detected

Abstract: Auditory integration training and a control treatment were provided for 16 children with autism in a crossover experimental design. Measures, blind to treatment order, included parent and teacher ratings of behavior, direct observational recordings, IQ, language, and social/adaptive tests. Significant differences tended to show that the control condition was superior on parent-rated measures of hyperactivity and on direct observational measures of ear-occlusion. No differences were detected on teacher-rated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…The most recent and most appropriately designed trials have demonstrated no significant benefit of dimethylglycine, 219,220 vitamin B 6 and magnesium, 221,222 or auditory integration training. [223][224][225] Both positive 226 and negative 227,228 results have been described for small, methodologically flawed studies of intravenous immunoglobulin. A recent double-blind, placebo-controlled trial revealed no statistically significant differences on Aberrant Behavior Checklist subscale scores between small groups of children with ASDs who were given omega-3 fatty acids and those who were given placebo.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…The most recent and most appropriately designed trials have demonstrated no significant benefit of dimethylglycine, 219,220 vitamin B 6 and magnesium, 221,222 or auditory integration training. [223][224][225] Both positive 226 and negative 227,228 results have been described for small, methodologically flawed studies of intravenous immunoglobulin. A recent double-blind, placebo-controlled trial revealed no statistically significant differences on Aberrant Behavior Checklist subscale scores between small groups of children with ASDs who were given omega-3 fatty acids and those who were given placebo.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…Meta-analysis was not possible due to very high heterogeneity or the presentation of data in unusable forms. Three studies Zollweg 1997;Mudford 2000) did not demonstrate any benefit of auditory integration therapy over control conditions. Three studies (Veale 1993;Rimland 1995;Edelson 1999) reported improvements at three months for the auditory integration therapy group based on the Aberrant Behaviour Checklist, but they used a total score rather than subgroup scores, which is of questionable validity, and Veale's results did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 94%
“…The number of participants in the seven studies ranged from 10 (Veale 1993) to 80 ; most studies had 20 or fewer participants (see the Characteristics of included studies table). Three of the studies included both children and adults (Rimland 1995;Zollweg 1997;Edelson 1999); while the remainder included only children aged three to 17 years (Veale 1993;Mudford 2000;Corbett 2008). Different diagnostic definitions of autism were used for inclusion of participants.…”
Section: Included Studiesmentioning
confidence: 99%
“…In connection with extreme sensitivity to sound, autistic children may have difficulty in following intentional instructions. These children experience difficulty in oral communication which may restrain them from following simple commands which may lead to communicative problems (Attwood, 1993;Piggot & Anderson, 1993;Kavon & McLaughlin, 1995;Bettison, 1996;Hughes, 1996;O'Neill & Jones, 1997;Duchan, 1998;Grandin, 1998;Huebner & Emery, 1998;Koegel et al, 1998;Gresham et al, 1999;Mudford et al, 2000;Anonim, 2003;Fazlioglu, 2003).…”
Section: Auditory Problemsmentioning
confidence: 99%